2017
DOI: 10.1177/0004867417743343
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy in the continuation and maintenance treatment of depression: Systematic review and meta-analyses

Abstract: There are only a few randomized trials of continuation electroconvulsive therapy and maintenance electroconvulsive therapy. The preliminary and limited evidence suggests the modest efficacy of continuation electroconvulsive therapy and maintenance electroconvulsive therapy with concomitant pharmacotherapy in preventing relapse and recurrence of depressive episodes for 1 year after the remission of index episode with the acute course of electroconvulsive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 37 publications
3
51
0
7
Order By: Relevance
“…8 In a recent meta-analysis study that included five studies with 436 patients, continuation and maintenance ECT with pharmacotherapy showed fewer relapses and recurrences than did pharmacotherapy alone within a year after successful completion of ECT. 9 A meta-analysis study reported that the relapse rate within one year following ECT exceeded 50%, and when placebo only was given to the patients after the end of ECT, the relapse rate reached 84%. 8,10 Although results from randomized controlled studies are needed for more rigorous evidence, maintenance ECT alone or combination with medication seems to be a reasonable treatment option for preventing relapse after ECT.…”
Section: Results Maintenance Therapy For Preventing Relapse After Ectmentioning
confidence: 99%
“…8 In a recent meta-analysis study that included five studies with 436 patients, continuation and maintenance ECT with pharmacotherapy showed fewer relapses and recurrences than did pharmacotherapy alone within a year after successful completion of ECT. 9 A meta-analysis study reported that the relapse rate within one year following ECT exceeded 50%, and when placebo only was given to the patients after the end of ECT, the relapse rate reached 84%. 8,10 Although results from randomized controlled studies are needed for more rigorous evidence, maintenance ECT alone or combination with medication seems to be a reasonable treatment option for preventing relapse after ECT.…”
Section: Results Maintenance Therapy For Preventing Relapse After Ectmentioning
confidence: 99%
“…In unserer Analyse war der rückfallpräventive Effekt der Kombination aus E-EKT und Pharmakotherapie der alleinigen Pharmakotherapie überlegen. Dies steht im Einklang mit anderen Studien [3,4,21] und zwei systematischen Reviews [22,23]. In den ersten drei Monaten nach der Akutbehandlung erlitten 40 % der Patienten ohne E-EKT in unserer Untersuchung Rückfälle vs. 10 % mit E-EKT (▶Abb.…”
Section: Diskussionunclassified
“…Electroconvulsive therapy (ECT) is the most effective treatment for TRD, but it requires 6-18 treatments under general anesthesia. 8 ECT reduces psychiatric hospitalization rates, long-term suicide risk, and all-cause mortality. 9 However, ECT is also associated with significant side effects and adverse events including nausea, headache, muscle pain, oral lacerations, dental injuries, and persistent myalgia.…”
Section: Introductionmentioning
confidence: 99%